Cell Cycle Regulators in Cancer: A Review - Swarup K Panda; Subhashree Ray; Sarthak R Nayak; Sudeshna Behera; Sangeeta S Bhanja; Viyatprajna Acharya (Achievements and Challenges of Medicine and Medical Science Vol. 4, 2024)
A recent in-depth view of cell cycle regulation and cancer has provided novel samples of research at the “Frontiers of Science.” However, the number of foremost revealing information about both topics has been derived from the intersection of these two fields. Genomic integrity is required to maintain long life and prevent diseases associated with genomic instability such as “cancer.” The cell cycle is a compilation of well-organized, sequential molecular events, that lead to succession of DNA replication and segregation of replicated chromosomes. Checkpoint is an important control point present in the cell cycle where stop and start signals can regulate the cell cycle. Cell cycle checkpoints are the strict regulatory mechanisms that monitor the order, integrity, and fidelity of the main events of the cell cycle. These include growth up to the acceptable cell size, replication, and integrity of the chromosomes, and their accurate segregation in due course of mitosis. Many of these mechanisms are highly conserved, while other studies on higher organisms have shown to control alternative cell fates with a significant impact on tumor suppression. Here, these different checkpoint pathways in a cell cycle and the consequences of their dysfunction on the fate of a cell has been taken into consideration. Undoubtedly, the hidden aspects of checkpoint signaling can be further explored with the help of an ever-growing arsenal of highly sophisticated experimental tools and techniques, which will enable us to get a more clear and complete picture of the remarkable fidelity of the cell cycle.